Psilotris vantasselli, a new species of goby from the tropical western Atlantic (Teleostei: Gobiidae: Gobiosomatini: Nes subgroup) - Tornabene, Luke; Baldwin, Carole C. (Zootaxa, 2019)
A new species of goby is described from submersible and scuba collections off Bonaire and New Providence Island, Bahamas. A molecular phylogenetic analysis of mitochondrial and nuclear genes confirms the placement of the new species within the genus Psilotris of the Nes subgroup of the Gobiosomatini. The new species is easily distinguished from congeners and morphologically similar species of Varicus by its unique coloration, which includes eight narrow, bright yellow bars on the trunk, each with a small orange spot centered on the lateral midline. In addition, the combination of the absence of scales on the head and body and the presence of modified ctenoid scales on the base of the caudal fin, branched pelvic-fin rays, and 15–16 pectoral-fin rays further differentiates the new species from other species of Psilotris and Varicus.